An Analytical Study of the Lex Favor Reo Principle in the Context of Corruption Case Resolution under the Third Amendment to the State Owned Enterprises Law in Indonesia - Fauzan Prasetya; Milda Istiqomah; Bambang Sugiri; Aiden L. Moreau (Faculty of Law, Universitas Pekalongan, 2025)
This study analyzes the implications of Law No. 1 of 2025—the Third Amendment to the SOE Law—on the application of the lex favor reo principle in corruption cases involving State-Owned Enterprises (SOEs) in Indonesia. Using a normative juridical approach with analytical and conceptual methods, the research reveals that the amendment redefines SOEs, limits the auditing authority of the Supreme Audit Agency, and removes the automatic classification of SOE losses as state losses. As a result, the legal interpretation of “state financial loss” in corruption cases has shifted significantly, potentially narrowing the scope of criminal liability for SOE officials. This change may lead to the re-evaluation of ongoing corruption prosecutions, including possible sentence reductions or acquittals. The study highlights the complex interaction between corporate reform and criminal accountability, emphasizing the need for doctrinal coherence, legal certainty, and the protection of substantive justice within Indonesia’s evolving post-reform legal framework.